The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2139/ssrn.3710604
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Evidence for Transmission of COVID-19 by Children in Schools? A Living Systematic Review

Abstract: What is the evidence for transmission of COVID-19 by children in schools? A living systematic review Background It is of paramount importance to understand the transmission of SARS-CoV-2 in schools, which could support the decision-making about educational facilities closure or re-opening with effective prevention and control measures in place. MethodsWe conducted a systematic review and meta-analysis to investigate the extent of SARS-CoV-2 transmission in schools. We performed risk of bias evaluation of all i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…By the time of conducting this study, there were few studies focusing on SARS-CoV-2 spread in schools. [18][19][20] Most of the reported evidence consisted of cases studies of outbreaks in specific schools or reports of contact tracing of index cases in educational settings. Most of the studies reported low secondary attack rates in schools 4 21 but also some conflicting observations of outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…By the time of conducting this study, there were few studies focusing on SARS-CoV-2 spread in schools. [18][19][20] Most of the reported evidence consisted of cases studies of outbreaks in specific schools or reports of contact tracing of index cases in educational settings. Most of the studies reported low secondary attack rates in schools 4 21 but also some conflicting observations of outbreaks.…”
Section: Discussionmentioning
confidence: 99%